Factors affecting ATM usage in India: An empirical analysis - Shariq Mohammed (UTMS Journal of Economics, 2012)
This study aims at identifying the factors affecting the customers demand for ATM services, by analyzing sample of 450 consumers' responses who have been interviewed personally through structured survey in 3 districts of Uttar Pradesh India. The results indicate that graduated and employed male customers who belong from higher income groups and having a bank account preferably in public sector bank are greatly emphasized to use of the banking services. Significant positive influence of the characterized socio-economic attributes on the use of ATM service was found. The service occupied customers significantly more emphasized to the use of ATM services. Noticeable, the banking attributes such as account type, convenience, number of services offered, and cost of banking services don't have very attentive influence on the use of advanced IT based banking services.
Keywords: O32; O31; 330; ATM services; regression analysis; logit model; technology and innovation; consumer usage; customers satisfaction